Heterocontrole da fluoretação das águas de abastecimento público de São Luís, Maranhão, Brasil. - Paredes, Suyene de Oliveira (2009)
The concentration of fluoride in public water supply systems must be maintained within the ideal range to ensure prevention of dental caries, without exposing the population to the risk of developing dental fluorosis. The objectives of this research were: to monitor the concentrations of fluoride in public water supply of São Luís, Maranhão, Brasil, from February 2008 to January 2009; and perform the mapping of residual levels of fluoride in isolated wells. Forty sampling points were conveniently selected, representing 39 districts of the municipality. The points were selected from areas of the company responsible for public water supply and also due to the proximity to the existing elevated tanks. For the mapping, it was considered estimated 20% of the wells considered in the areas of performance. The analysis of the fluoride concentration was performed in triplicate, using the combined electrode ion-specific for fluoride (ORION 9409BN) and reference electrode (ORION 900200), connected with the potentiometer ORION 710 A, previously calibrated. After analyzed, the samples were considered adequate when the fluoride concentration was within the recommended limits from 0.60 to 0.80 ppm F (criterion I) or within the stipulated range of 0.55 ppm to 0.84 ppm F (criterion II). The results showed, in fluoridated locations, large variation between the minimum and maximum concentrations. Considering the whole, the average for the city was 0.58 ppm F (± 0.24) and median 0.61 ppm F, with minimum 0.02 ppm F and maximum 1.33 ppm F. Of the 480 samples, the highest percentage was considered inadequate (62.9%) by criterion I, while the criterion II was 48.3%. Regarding the mapping, we observed residual fluoride levels below 0.11 ppm in the waters of isolated wells. We conclude that there was unequal access to fluoridated water by the population Ludovicense. The fluoridation program in São Luís-MA needs improvement. Therefore, surveillance measures based on external control and operational control becomes essential to ensure the efficacy and effectiveness of the method.